The Irony Analysis of The Amulet of Samarkand by Jonathan Stroud - Latifah, Meifithriana (Journal of Literature, Linguistics, & Cultural Studies, 2022)
One of literary devices that can be applied to literary works is irony. The irony as literary device is a figure of speech in which the speaker’s meaning is far from the usual meaning of the words or quite the opposite. In this study, the author analyzed the irony in novel The Amulet of Samarkand, to get in-depth explanation of the types of irony in the novel, how it was portrayed and how it was connected to the plot of the story. Furthermore, this study was part of literary criticism since the researcher analyzed the literary work by new criticism theory. The data were interpreted and analyzed using Kennedy’s theory of irony (1991). The findings revealed that there were five kinds of irony found in the novel, which included verbal irony, dramatic irony, cosmic irony, situational irony, and ironic point of view. The researcher also found that each of the irony worked to the plot as it played roles as an agent to move the plot to its rising action and climax, and it worked to emphasize some important points in the plot as well. The important points in the plot that were emphasized by the irony covered the naivety of Nathaniel, the discrepancy of the thing being done and its result, and the cunny nature of the demon.